Rhythmic training, literacy, and graphomotor skills in kindergarteners - Frey, Aline; Lessard, Andrée; Carchon, Isabelle; Provasi, Joëlle; Pulido, Loïc (Frontiers in Psychology, 2022)
The aim of this manuscript is twofold: first, to investigate the relationship between rhythmic, phonological and graphomotor skills in kindergarten children; and second, to evaluate the possible impact of rhythmic training on the two other skills. To that end, we selected a sample of 78 children in Québec. Forty-two children received rhythmic training (experimental group) and 34 arts training (active control group) during the same period (10 weeks). Before and after training, children in both groups were assessed for general skills (forward and backward memory span, vocabulary, non-verbal ability), rhythmic skills (synchronization and discrimination tasks), literacy skills (phonological skills - syllable counting, syllable deletion, rhyme discrimination – and invented spelling skills) and graphomotor skills (legibility of letter writing, quality of copying of geometric shapes). Results showed correlations between the child’s rhythmic and literacy skills, as well as between rhythm synchronization and pen pressure. In addition, rhythmic training showed improvement in rhythmic abilities, but this did not transfer to literacy or graphomotor development (apart from a significant increase in the duration of pauses in both groups at post-test, with a larger improvement for the rhythm group). These results are discussed in terms of duration and intensity of learning, and they highlight the possible benefits of informal rhythm practices in the classroom.